A cognitive study of body fat percentage in humans by anatomization of LIPID profile, bio-electric impedance and clustering using k-means algorithm - Grace Hannah, J; D. Gladis, Dr (International Journal of Engineering and Technology, 2018)
The pathogenesis of obesity and overweight delves fathomlessly into a personâ€™s physical activities, food habits and their genetic inher-itance. Infelicitously a substantial number of population have moved to urbanization with shifts towards less physical work, exercise and diets high in saturated fats and sugars paving the way for the soaring rise in corpulence amongst individuals. Multifarious prodigious stud-ies have been done on the perennial concerns caused due to obesity. Due to the scathing health lurgies that have originated in recent times, a punctilious exploration of body fat percentage for an individual has become imperative. The quondam work anent body fat percentage in-volved a formula comprising of Body Mass Index (BMI), age and gender of a person. The anatomical conformation of an individual unrav-eling the fat constitution, and the muscle-tissue composition is not construed by using BMI. Thus the formula dampers the veracity for a person having more muscle mass than fat mass, and speciously vitiates the fat percentage of that person. The proposed study escalates the coherence and efficacy of the body fat percentage for a person by entailing the lipids from the blood test, the subcutaneous and the visceral fat values obtained from a Bio-Electric Impedance method in the formula. The ethical committee approval for this study has been obtained from the Institutional Ethics Committee, Madras Medical College, and Chennai. This pragmatic study has been statistically analyzed using R-tools and the results have been successfully acquired.Â Â
Keywords: Obesity; Body Fat Percentage; BMI; Bioelectric Impedance; R-Tools